1982
DOI: 10.1002/1097-4679(198207)38:3<601::aid-jclp2270380322>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

MMPI-derived indicators of organic brain dysfunction

Abstract: For more than a decade researchers have been attempting to develop a reliable and valid way in which the MMPI can be used as an indicator of organic brain dysfunctioning. This investigation reviews the major approaches and tries all of them on a sample of 32 organic and 34 schizophrenic hospital patients. Results show that the MMPI methods used assigned patients correctly in 45 to 76% of cases. The Sc scale of the MMPI was generally superior to other scales. Most methods predicted better for women than for men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The second procedure was to examine data from studies of patients other than those with epilepsy. Published information (Heaton et al, 1978;Sillitti, 1982) identify only limited positive findings and the studies concluded that ". .…”
Section: Do Underlying Brain Problems Create a Basis For Abnormal Or mentioning
confidence: 99%
“…The second procedure was to examine data from studies of patients other than those with epilepsy. Published information (Heaton et al, 1978;Sillitti, 1982) identify only limited positive findings and the studies concluded that ". .…”
Section: Do Underlying Brain Problems Create a Basis For Abnormal Or mentioning
confidence: 99%
“…Unfortunately, this group's description of their encouraging results as negative apparently influenced other writers, such as Trifiletti (1982), who listed their work as evidence that argued against the clinical use of the scale. Sillitti (1982) administered a shortened form of the Sc-0 scale that contained only 48 of its 80 items to brain-damaged and schizophrenic patients at a small, private hospital. Despite his deletion of 32 items, a Fisher p and a t run by the present author on Sillitti's data yielded a highly significant (p <.01) difference in the percentages of the two groups' members who scored above/below his cutting score and a between-means difference significant far beyond the .OOl level.…”
mentioning
confidence: 99%
“…The scale should not be used on female samples at present. Sillitti (1982) reported a good hit rate (73%) with his female Ss, but Watson (1971) found the scales ineffective with his women. Both used relatively small samples.…”
mentioning
confidence: 99%
“…The findings of this study suggest that caution is necessary in applying these MMPI scales to outpatient brain-damaged, schizophrenic, somatoform, and brain-damaged schizophrenics. As was noted earlier, previous studies (Golden et al, 1979;Graca et al, 1984;Sillitti, 1982) had only examined inpatient groups of brain-damaged and schizophrenic individuals. Given the different status of these patients, of course, some differences could be expected reasonably.…”
Section: Discussionmentioning
confidence: 98%
“…Two studies (Dodge & Kolstoe, 1971;Schwartz & Brown, 1973) successfully cross-validated the P-N Scale. Golden, Sweet, and Osmon (1979), Sillitti (1982), and Graca, Hutzell, Gaffney, and Whiddon (1984) have examined these three scales in the task of differentiating braindamaged from schizophrenic groups of inpatients. While some of these studies (Golden et al, 1979, Sillitti, 1982) demonstrated a role for the Schizophrenia (Sc) scale of the MMPI (Hathaway, 1956) in differentiating schizophrenic and brain-damaged groups, these same studies were faulted by Watson (1984) on numerous methodological grounds.…”
mentioning
confidence: 99%